Humanitarian Aid Workers’ Mental Health and Duty of Care - Jachens, Liza (Eur J Psychol, 2019)
Set in challenging and complex environments, there has been growing concern about the mental health consequences of aid work. Along with existing difficulties in reducing well-known occupational risks such as exposure to trauma, there is a lack of awareness of psychosocial risks in the humanitarian sector. This paper is a discussion, drawing on occupational health perspectives, on ways to reflect on mental health policies, research and interventions in this sector.